Degradation of Incoloy‐800HT in molten FLiNaK salt at high temperatures. Issue 5 (20th January 2022) - Harinath, Yadavalli V.; Chandramohan, P.; Anandkumar, B.; Mohan, T. V. Krishna; Rangarajan, S.; Albert, Shaju K.
Abstract: Many studies have revealed that Hastelloy‐N is the most suitable material for molten FLiNaK salt application. However, due to the nonavailability and high cost of Hastelloy‐N, Incoloy‐800HT is being considered as an alternate material. Corrosion studies were carried out on Incoloy‐800HT in vacuum‐dried molten FLiNaK salt at 650°C and 750°C for 100, 250, 500 and 1000 h. The exposed specimens were examined for weight loss and subjected to surface analysis using techniques like metallography, confocal laser scanning microscopy, X‐ray diffraction and laser Raman spectroscopy. The results revealed that the weight loss and depth of attack are less in specimens exposed to 650°C than those exposed to 750°C, and there is no evidence of any localised attack at both the temperatures. Chemical analysis of the used salt showed higher Cr and Fe contents than that in fresh salt, indicating dealloying of elements like Cr and Fe from Incoloy‐800HT specimens during exposure to molten FLiNaK salt. Oxides rich in Fe and Cr with spinel‐type crystal structures were identified on the exposed surfaces. From the results, it could be concluded that though there was considerable corrosion of Incoloy‐800HT, the material may be used in static molten FLiNaK salt systems with limited design life restricted to a temperature of 650°C by giving appropriate corrosion allowance. Abstract : Corrosion studies on Incoloy‐800HT in molten FLiNaK salt of up to 1000 h at 650°C revealed that there was no localised attack on specimens; the corrosion rate was 254 µmpy with a depth of attack of up to 50 µm. Though generally, Incoloy‐800HT has a high corrosion rate in a FLiNaK environment, the study concluded that the material may be used for static molten salt systems of up to 650°C by providing appropriate corrosion allowance.